Decorated Dyck Paths, Polyominoes, and the Delta Conjecture - D'Adderio, Michele; Iraci, Alessandro; Wyngaerd, Anna Vanden (Memoirs of the American Mathematical Society, 2022)
We discuss the combinatorics of decorated Dyck paths and decorated parallelogram polyominoes, extending to the decorated case the main results of both Haglund (“A proof of the